Characterization of Viscoelastic Properties Considering the Nonrelaxation for Filled Rubber - Xinyi Lin; Mengxi Huang; Yang Wang; Ziran Li (Advances in Polymer Technology)
The influence of nonrelaxation on the Payne effect of carbon black-filled rubber is studied. The prestrain is introduced in the Kraus model in the form of exponential growth. Combined with studies of temperature correlations, an explicit model for predicting the Payne effect at different prestrains and temperatures is developed. Dynamic mechanical analyses are performed to determine model parameters and validate the proposed model. To further verify the proposed model, the heat buildup of rubber columns under dynamic tensile load is tested and simulated. The comparison between simulated and measured data shows that the simulation considering nonrelaxation is more accurate than without considering. With the increase of prestrain, the accuracy of considering nonrelaxation becomes more obvious.